β-endorphin immunoreactivity during anaesthesia in equidae - Taylor, P. M. [UNESP]; Vet, M. A. [UNESP] (Elsevier, 2000)
Objective To determine the effects of surgery, hypoxia, hypercapnia and flunixin administration on plasma β-endorphin immunoreactivity (BEI) in anaesthetized horses. Study design Prospective crossover study. Animals Six healthy adult Welsh Mountain ponies and seven healthy adult Thoroughbreds. Methods Ponies were anaesthetized with thiopentone and halothane or with pentobarbitone and the horses with guaiphenesin, thiopentone and halothane. Ponies were anaesthetized for 2 hours and on separate occasions underwent a period of hypoxia, hypercapnia, anaesthesia only, or were given flunixin at induction. The horses were anaesthetized for 2 hours and on separate occasions underwent surgery to relocate one carotid artery subcutaneously or anaesthesia only. Plasma samples were taken pre-anaesthesia, at 20 minute intervals during, and after anaesthesia for BEI assay using radio-immunoassay. Analysis of variance of the concentration-time curve was used for statistical analysis. Results Pre-anaesthetic β-endorphin immunoreactivity (BEI) values ranged between 5.7 and 20.4pmol L−1.Induction of anaesthesia caused a five to 10 fold increase in mean plasma BEI in all cases except the hypercapnia group. Halothane anaesthesia increased BEI in ponies and horses but there were no significant changes during pentobarbitone anaesthesia. The increase in BEI in the hypoxic group was greater (peak value 136.8± 32.2pmol L−1) and sustained for a longer period compared with levels in those given halothane alone or in those which became hypercapnic. There was marked individual variation in the flunixin group and changes were not significant. Surgery in the horses resulted in the highest peak values in the study (182.5±153.0pmol L−1) but the AUC was not significantly higher than in the same animals without surgery, where the peak value was 102.9±42.1pmol L−1.Conclusions Beta-endorphin appeared to be a sensitive marker of an endocrine stress response but its physiological role during equine anaesthesia is unknown. Clinical relevance Unknown. © 2017 Wiley. All rights reserved.
Keywords: Anaesthesia; Horse; Stress response; β-endorphin immunoreactivity